Sanjiangyuan Eco-immigrants: lifestyle, social adaptation, change of idea and urbanization process - Shi, Desheng; Yang, Zicong (Frontiers in Sustainable Cities, 2023)
This paper describes the living conditions of the ecological migrants in Sanjiangyuan in the process of rapid urbanization and discusses the impact of urbanization on them through social adaptation and conceptual changes. Then we argue that: due to the lack of prominent diversity of immigrant lifestyles, little social mobility, low occupational differentiation, and "heterogeneity," the lifestyles have heavy traditional characteristics; In addition, due to rapid urbanization, immigrants experience "cultural oscillation" in cultural and social adaptation, and the phenomenon of "marginal personality" appears in personality. However, due to the slow process of rationalization and secularization, and the market economy and urban lifestyle have not yet been formed, the urbanization degree of ecological immigration is at the primary level.